Utilization of Digital Marketing to Improve Sales Volume of MSME's Products - Nafiuddin Nafiuddin; Hamdan Hamdan (Journal of Digital Marketing and Halal Industry, 2020)
Micro, Small, Medium Enterprise (MSME's) marketing is still limited to traditional models and has not yet utilized digital marketing optimally. The purpose of this article is to identify the use of social media to increase the sales volume of MSME's products. This article uses the literature study method, using secondary data. Data analysis techniques used a descriptive approach. The results of studies and analysis show that the importance of using social media such as Collaborative projects (Example: Wikipedia), content communities or sharing media such as YouTube, social networking sites (example: Facebook), and virtual social worlds or market places such as open outlets, Tokopedia, and shopper. Optimizing social media can increase market share and sales of MSME's products.